1982
DOI: 10.1161/01.hyp.4.3_pt_2.106
|View full text |Cite
|
Sign up to set email alerts
|

Renal prostaglandins and the control of renin release.

Abstract: multifactorial. Stimuli for renin release act through three groups of mechanisms which include: 1) two intrarenal receptors, the renal vascular receptor in the afferent arteriole and the macula densa; 2) the renal nerves and a renal 0-adrenergic receptor; and 3) a group of humoral agents.1 In the past decade, attention has been focused on the potential role of the renal prostaglandins in renin release, both as primary stimuli*" 1 and as essential mediators in stimulus-secretion coupling for the renal vascular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

1984
1984
2005
2005

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The rise in renin release was attributed to renal ischemia or to strong activation of renin release mechanisms overcoming the inhibitory effect of indomethacin at low perfusion pressure. However, sympathetic stimulation probably became more intense as the renal arterial perfusion pressure was lowered in the conscious dogs studied by Freeman et al (1982) and in the anesthetized dogs with innervated kidneys studied by Blackshear et al (1979). In support of this explanation, Romero et al (1976) found a large increase in renin release in rabbits after extensive bleeding both before and after indomethacin administration.…”
Section: Adrenergic Stirnulationmentioning
confidence: 89%
See 2 more Smart Citations
“…The rise in renin release was attributed to renal ischemia or to strong activation of renin release mechanisms overcoming the inhibitory effect of indomethacin at low perfusion pressure. However, sympathetic stimulation probably became more intense as the renal arterial perfusion pressure was lowered in the conscious dogs studied by Freeman et al (1982) and in the anesthetized dogs with innervated kidneys studied by Blackshear et al (1979). In support of this explanation, Romero et al (1976) found a large increase in renin release in rabbits after extensive bleeding both before and after indomethacin administration.…”
Section: Adrenergic Stirnulationmentioning
confidence: 89%
“…That prostaglandins and 8-adrenergic agonists are independent stimulators of renin release may explain the observations of Blackshear et al (1979) in studies on anesthetized dogs and of Freeman et al (1982) on conscious dogs. Both groups observed that indomethacin inhibited renin release during reduction in the renal arterial perfusion pressure only within the range of autoregulation.…”
Section: Adrenergic Stirnulationmentioning
confidence: 94%
See 1 more Smart Citation